Towards an Edupreneurial Indonesian Higher Education: A Culturepreneur Paradigm - Soeparto, Wahyudi Henky (Universitas Airlangga, 2025)
This paper explores the rise of edupreneurial culturepreneurship within Indonesian higher education institutions (HEIs), where students and faculty transform cultural production into entrepreneurial ventures, and intertwine entrepreneurial motivation with cultural a/effect. Drawing on publicly available data—university programs, national student entrepreneurship schemes, and online cultural initiatives—this study maps how Indonesian HEIs serve as incubators for creative economic activity. Case studies include Ritus Liyan initiative, ISI Yogyakarta’s art commercialization programs, and Universitas Ciputra’s entrepreneurial mindset. Findings reveal both opportunities and tensions in merging artistic expression with business models. The growing acknowledgement of entrepreneurial significance in multidisciplinary level, however, is not properly manifested with echo of Cultural (with big C) sensitivity. “Culture” serves as a paradigmatic underpinning that reminds entrepreneurs to go beyond numerical and/or quantitative profit as the sole indicator of success. Thus, this study contributes a framework for understanding universities as agents of cultural innovation in Indonesia’s evolving creative economy landscape and critiquing the semantic banality of the term ‘Entrepreneurship’.